An Act for regulating the fur trade, and establishing a criminal and civil jurisdiction within certain parts of North America [electronic resource]. - Great Britain. An Act for Regulating the Fur Trade, and Establishing a Criminal and Civil Jurisdiction within Certain Parts of North America. (London : G. Eyre and A. Strahan, 1821)
Includes marginal notes. Caption title. At head of title: Anno primo & secundo Georgii IV. regis. Cap. LXVI. "[2d July, 1821.]." Electronic reproduction. Mode of access: Internet. 44